Stimuli-responsive multifunctional glyconanoparticle platforms for targeted drug delivery and cancer cell imaging. Issue 5 (30th March 2017) - Wu, Xumeng; Tan, Yu Jia; Toh, Hui Ting; Nguyen, Lan Huong; Kho, Shu Hui; Chew, Sing Yian; Yoon, Ho Sup; Liu, Xue-Wei
Abstract : A targeting system with excellent targeting ability is constructed by incorporating carbohydrate-modified gold nanoparticles as vehicles and GSH-responsive species as the payload. Abstract : Targeted bioimaging or chemotherapeutic drug delivery to achieve the desired therapeutic effects while minimizing side effects has attracted considerable research attention and remains a clinical challenge. Presented herein is a multi-component delivery system based on carbohydrate-functionalized gold nanoparticles conjugated with a fluorophore or prodrug. The system leverages active targeting based on carbohydrate–lectin interactions and release of the payload by biological thiols. Cell-type specific delivery of the activatable fluorophore was examined by confocal imaging on HepG2 cells, and displays distinct selectivity towards HepG2 cells over HeLa and NIH3T3 cells. The system was further developed into a drug delivery vehicle with camptothecin (CPT) as a model drug. It was demonstrated that the complex exhibits similar cytotoxicity to that of free CPT towards HepG2 cells, and is significantly less cytotoxic to normal HDF and NIH3T3 cells, indicating excellent specificity. The delivery vehicle itself exhibits excellent biocompatibility and offers an attractive strategy for cell-type specific delivery depending on the carbohydrates conjugated in the system.